Increasing biodiversity in wood-pastures by protecting small shrubby patches - Oksuz, Duygu P. (2022)
Wood-pastures are grazed systems, widespread across Europe, where natural and economic values often co-exist. Social and economic changes in Europe generate both threats and opportunities to these systems, calling for new or improved management strategies. We studied the potential of increasing the biodiversity of wood-pastures through the promotion of small-scale habitat diversification. More specifically, we evaluated the impact of protecting very small shrubby patches within large Mediterranean wood-pastures. We sampled species assemblages of plants, lichens and coleopterans in 13 small patches (252–3000 m2) with a well developed shrub layer, and 11 plots in the adjacent matrix of virtually shrub free wood-pasture. Despite their very small size, patches had clearly distinct assemblages of all the studied taxa and their presence greatly enhanced the species richness of the studied wood-pasture landscapes. The presence of shrubby patches increased species richness in wood-pastures by 42% for plants, 27% for lichens and 29% for coleopterans (average over two study areas), a very substantial gain considering that patches covered less than 0.5% of the studied wood-pastures. Our results indicate that the protection and promotion of even small shrubby patches is a promising low-cost nature-based strategy to increase the biodiversity value of wood-pasture landscapes, without substantially affecting the economic value of this silvopastoral system, which is an old and important part of the natural and cultural heritage of Europe.